Application development and practice model for radiation education. Issue 3 (4th August 2022) - Tokumoto, Ieyasu; Hirozumi, Toyokazu; Sakai, Masaru; Nishiwaki, Junko; Kato, Chihiro; Watanabe, Kunio; Mizoguchi, Masaru; Ishikawa, Yohei
Abstract: Since the nuclear disaster in Fukushima, Japanese soil scientists have tackled soil contamination problems due to radioactive cesium. For the radiation education based on the research results and outreach activities, we published a comic book and developed a digital application using iOS Xcode for Apple iPhone and tablet devices. This allows students to quickly understand why clay soil absorbed cesium and how to remove contaminated soil using educational mini‐games. Through radiation education seminars and a conference, our application was evaluated and revised by school teachers.